A study on metrosexuality and its relationship to body image, self-esteem and gender role conflict among Filipino males - Reyes, Miguel Carlos M. (Animo Repository, 2010)
The metrosexual male is very much blooming in society today, as being straight men who are very much concerned with their body image. These men tend to be mistaken for homosexuals mainly because they are not able to achieve the gender role they are perceived to play. On the other hand, self-esteem uplifts the body image of the individual. It is the aim of this research study to give a better grasp of the importance of body image for metrosexuals as well as to give a deeper understanding of the gender roles they assume to play and the conflicts that come in line with that. A focus group discussion was conducted, which was used to generate a metro sexuality scale, which was administered to forty (40) metrosexual males together with three (3) other tests to measures the variables of body image, self-esteem and gender role conflict. Result show that self-esteem serves as a predictor of body image as well as metro sexuality was found to be positively related to body area satisfaction under body image.